Perbandingan Sistem Administrasi Negara Lebanon Dengan Negara Turki - Fabita M.R., Chesa (Institut Riset dan Pengembangan Indonesia, 2024)
The state becomes a forum so that people can live their lives well and maintain social peace. Lebanon and Turkey have their own characteristics and systems for running life, of course there are differences from a social, economic and political perspective. This research aims to compare and describe the state administration system of Lebanon and Türkiye. The research was carried out using qualitative methods in the nature of library research. Data sources come from journal articles, literature, online mass media, and the Internet. The data collection technique in this research is documentation, through written remains, especially in the form of archives and including books about opinions, theories, propositions, concepts or laws related to research problems. The research results show that this research reveals several comparisons between Lebanon and Turkey in various political, economic, legal and administrative aspects. Lebanon and Turkey are both developing countries with internal challenges that include conflict, sector-specific dependencies, and immature infrastructure. However, the political approaches and philosophies of both countries have significant differences.